2020
DOI: 10.1093/jas/skaa265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and mitigation of the effects of in utero heat stress on piglet growth performance, postabsorptive metabolism, and stress response following weaning and transport

Abstract: In utero heat stress (IUHS) increases energy requirements of pigs during postnatal life, and this may compound weaning and transport stress. The study objective was to evaluate and mitigate the negative effects of IUHS following weaning and transport through the provision of a nutrient dense (ND) nursery diet formulated to meet the greater energy requirements of IUHS pigs during the first 14 d post-weaning and transport. Twenty-four pregnant gilts were exposed to thermoneutral (TN; n = 12; 17.5 ± 2.1°C) or hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 34 publications
1
28
1
1
Order By: Relevance
“…Increased temperatures and heat waves due to the changing climate have negatively affected the animal industry [ 1 , 2 ]. In such conditions, livestock can suffer heat stress (HS) that may severely reduce carcass quality via reduced lean growth and increased fat content [ 3 , 4 ]. The HS reduces the growth rate of livestock by lowering feed intake and it causes an imbalance in physiological responses such as blood metabolic indicators, respiration rate, nutrient metabolism, and rectal temperature [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased temperatures and heat waves due to the changing climate have negatively affected the animal industry [ 1 , 2 ]. In such conditions, livestock can suffer heat stress (HS) that may severely reduce carcass quality via reduced lean growth and increased fat content [ 3 , 4 ]. The HS reduces the growth rate of livestock by lowering feed intake and it causes an imbalance in physiological responses such as blood metabolic indicators, respiration rate, nutrient metabolism, and rectal temperature [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors are known to contribute to the color of fresh meat products including chronic and acute stress pre-slaughter, glycolytic potential, genetics, among others [ 46 ]. As previously mentioned, IUHS has been associated with energy metabolism [ 4 , 9 , 10 ] and the stress response [ 9 , 11 , 12 ] in swine. However, it appeared such differences did not have any meaningful effect on oxidative stability shown by instrumental display color and TBARS values, nor on the extent of protein denaturation shown by transmission values.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted in parallel with Maskal et al [ 10 ], and detailed treatment information regarding live animals can be found there. Briefly, dams utilized in the study were first parity F1 Landrace × Large White gilts ( n = 24) sired by a single Duroc line (Choice Genetics USA, Des Moines, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations